A NEW PROFESSIONAL PROFILE? GENERAL THOUGHTS ON INDUSTRIAL ARCHAEOLOGIST IN THE XXI CENTURY - González Vergara, Óscar (2014)
This paper will discuss the role the industrial archaeologist needs to address contemporary heritage issues from a very specific theoretical and methodological paradigm: industrial archaeology or, more specifically, its evolution, contemporary archaeology. The world of the second half of the twentieth and twenty-first century requires from the Industrial archaeologist tools and methodologies that join and expand those already used with the heritage of the industrial revolution. This is a very favorable time to regenerate this scientific discipline.